The reality of environmental education in kindergartens in Tripoli from the teachers' point of view - Ghashir, Nadia Saad Khalifa (Tobruk University Journal of Social and Human Sciences, 2025)
The current study seeks to identify the reality of environmental education in kindergartens from the teachers’ point of view and to identify the significance of the differences in the level of their points of view according to the variables of the type of kindergarten (public/private), academic qualification, and number of years of experience.The epared a questionnaire consisting of (25) items distributed over six areas: the first area is personal hygiene and safety of the senses, the second is food, the third is security and safety in the kindergarten environment, the fourth is cleanliness and order of the kindergarten environment, the fifth is water and air, and finally the sixth area is caring for plants and animals.The results showed that the teachers agreed to a high degree on the availability of environmental education in the kindergartens included in the study. The results also showed that there were significant differences in the degree of agreement attributed to the variable of the type of kindergarten, and the differences were in favor of private kindergartens. The results also showed that there were significant differences in the degree of agreement attributed to the variable of the type of kindergarten, and the differences were in favor of private kindergartens. The results also showed that there were significant differences in the degree of agreement attributed to the variable of educational qualification. These results were discussed in light of the theoretical framework and previous studies, and a number of recommendations and suggestions were presented to complete the benefitdescriptive analytical approach was used, and the sample consisted of (100) female teachers from public and private kindergartens in the city of Tripoli. The researcher pr.